2008
DOI: 10.1143/apex.1.092302
|View full text |Cite
|
Sign up to set email alerts
|

A GaAs/AlAs Multilayer Cavity with Self-Assembled InAs Quantum Dots Embedded in Strain-Relaxed Barriers for Ultrafast All-Optical Switching Applications

Abstract: An optical Kerr signal has been simulated for GaAs/AlAs multilayer cavity structures by using the self-consistent transfer matrix method. Enhancement of the Kerr signal intensity was clearly demonstrated for the cavity mode (λ∼1504 nm) owing to the strong optical field in the multilayer cavity. The Kerr signal intensity can be further enhanced with the use of a higher nonlinear refractive index only for the half-wavelength (λ/2) cavity layer. We propose a GaAs/AlAs multilayer structure with the λ/2 cavity laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…In a previous study [6], the optical Kerr signal intensity was shown to be increased by two orders of magnitude when the nonlinear refractive index of the λ/2 cavity layer increased by only one order of magnitude. Furthermore, the nonlinear refractive index of the cavity layer is the main influence on the optical Kerr signals, although the optical intensity is distributed throughout the cavity layers, including the DBR layers, as shown in Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a previous study [6], the optical Kerr signal intensity was shown to be increased by two orders of magnitude when the nonlinear refractive index of the λ/2 cavity layer increased by only one order of magnitude. Furthermore, the nonlinear refractive index of the cavity layer is the main influence on the optical Kerr signals, although the optical intensity is distributed throughout the cavity layers, including the DBR layers, as shown in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…These results indicate that the strongly enhanced optical intensity due to the cavity effects plays an important role in the nonlinear optical response of the materials in the structure. In a previous simulation [6], we showed that the optical Kerr signal intensity depended strongly on the nonlinearity of the half-wavelength (λ/2) cavity layer despite being only a small fraction of the total cavity thickness.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…16 [69], with the possible trade-off of losing the large field enhancement at resonance. Alternatively, the experimental demonstration of the QD-based Kerr nonlinearity has been achieved with a resonance pumping scheme where a cross-Nicol configuration is applied [107,108]. Figure 7(a) shows the pump beam is 45 o polarized compared to the original polarization of the probe beam along the y-axis.…”
Section: Kerr Nonlinearitymentioning
confidence: 99%
“…We have demonstrated optical Kerr gate switches based on a GaAs=AlAs multilayer cavity with InAs quantum dots (QDs) embedded in strain-relaxed barriers. [10][11][12][13][14][15] The strong internal light electric field due to the cavity effects markedly enhances of nonlinear phase shift in the halfwavelength (λ=2) cavity layer containing QDs. Vertical geometry all-optical switches based on the reflectance modulation of conventional InAs QDs placed in a GaAs= AlAs multilayer cavity have also been demonstrate by Jin and coworkers.…”
Section: Introductionmentioning
confidence: 99%